Zihar (a form of divorce) and its negative effects on women, and the opinions of Islamic scholars on it (Al-Farooq Journal of Sciences, 2026)
This study examines the ruling of Zihar (injurious assimilation of the wife to a prohibited relative) in Islamic Sharia and its subsequent negative impacts on women. Utilizing an inductive and analytical methodology, the research scrutinizes primary Sharia texts and the legal consequences arising from this practice.The study posits that Zihar is a form of spousal abuse; while it does not inherently constitute a formal dissolution of marriage (Firqah), it effectively suspends the marital rights in a manner akin to an irrevocable divorce (al-Baynunah) for the duration of the ruling's effect. This is because Zihar renders sexual intimacy (wat’) unlawful, prohibiting the husband from approaching his wife as long as the status of Zihar persists, mirroring the prohibition faced by a man regarding his irrevocably divorced wife.Furthermore, the study characterizes Zihar as an injurious oath that obstructs marital relations. In the pre-Islamic era, it was considered one of the most detrimental forms of separation; if a man grew to dislike his wife but wished to prevent her from marrying another, he would pronounce Zihar, leaving her "suspended"—neither enjoying the rights of a wife nor being free to marry elsewhere.With the advent of Islam, and in alignment with its universal principles of eradicating injustice and safeguarding women's interests, the legal framework of Zihar was reformed. Islam maintained the root of the prohibition but reclassified its legal effect as a temporary prohibition contingent upon expiation (Kaffarah), thereby ensuring that the marital bond remains intact while providing a mechanism to rectify the harm.